Types and Determinants of Congenital Anomalies among Newborns in Bint Al-Huda Teaching Hospital in Thi-Qar Governorate at 2015-2017 - Ghada Mansoor Abood Al-Asadi (Journal of Global Pharma Technology, 2018)
Background: Congenital anomalies are a major cause of neonatal and infant death, and disability around the world. The prevalence of congenital malformations differs widely between countries. Objectives: To determine the types of congenital anomalies among neonates and to identify the possible risk factors associated with congenital anomalies. Patients and Methods: A case-control study was carried out during 3years period (from the 1st of January 2015 to the 15th of December 2017). One hundred seventy-two neonates with congenital anomalies admitted to neonatal intensive care unit in Bint Al-Huda Teaching Hospital were involved in the study as a case group. A total of 305 neonates without congenital anomalies were randomly selected from neonates admitted to the same hospital for reasons other than congenital anomalies and including in the study as a control group. Results: Neural tube defects are the predominant type of congenital anomalies (31.9%), followed by congenital heart diseases (14.5%), cleft lip and palate (6.9%), and upper and lower limbs deformity (5.9%). Both genders equally distributed among patient and control group p-value>0.05.The higher percentages of multiple congenital anomalies were detected among low birth weight neonates (30.6%), premature neonates (24.5%), neonates of mothers with advance age (> 35 years) (33.3%), grand multiparas (27.8%), and women with pregestational diabetes (37.5%).There is a significant positive association of low birth weight and premature neonates, young maternal age, chronic maternal illness, father occupation, and family history with the congenital anomalies, p-value < 0.05. Mother and Father Age, and prematurity were independent risk factors for congenital anomalies (OR 8.470, 17.367, 6.606, respectively). There is a highly significant association between congenital malformations with periconceptional folic acid intake, p-value <0.001, (OR 5.746). Conclusion: The commonest congenital anomalies are neural tube defects, followed by congenital heart diseases, cleft lip and palate, and upper and lower limbs deformity. There is a positive association of low birth weight, chronic maternal illness, father occupation, and family history with the congenital anomalies. Parental age and prematurity were independent risk factors for congenital anomalies. Periconceptional folicacidin take protect against congenital malformations.Keywords: Types, Risk factor, congenital anomalies.